THE IMPORTANCE OF GROWING ROLE OF GAMIFICATION, IN THE DEVELOPMENT OF CHILDREN'S E-LEARNING PROGRAMS - Dr. Navdeep Kumar Maurya (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Gamification is Powerful educational Teaching Technique in the digital education era. In this students get to learn while playing, get inspiration, Engagement and Participate by changing their behavior currently. Gamification is also a big educational market. Which reaches the customer through millions of tools or Apps. Both Structural and Content Gamification have their own Importance. Which the Learner chooses based on his age objective and activity. The use of Gamification makes it easier for Teachers to explain content and the students take it with Joy and dedication and develop their life skills. It has Great importance in e-learning also. But gamification causes a Lot of distraction in children which is also a drawback, there are some other drawback as well. If this is done under the supervision of Teachers, School and Parents then it can be a boon for the Student's future.